2014
DOI: 10.4172/2376-0214.1000127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Diversity of Culturable Thermotolerant Bacteria from Four Hot Springs of India

Abstract: The culturable bacterial diversity of four hot springs of India was analysed, employing different media and screened for temperature tolerance (40°C -70°C). Sixty morphotypes from Bakreshwar, 48 from Balrampur, 46 from Chumathang and 52 from Vashist were obtained. A set of 112 isolates, tolerant to 45°C and above, were analysed employing Amplified ribosomal DNA restriction analysis (ARDRA). Sequencing of 16S rRNA gene of the representative isolates revealed that 86%, 93%, 44% and 44% of the isolates respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…There are studies supporting and substantiating findings of the present study that bacterial communities in the hot springs located on the high altitude are dominated by Proteobacteria [12]. Similar observations have been made by [13,14] that geographic locations play a significant role in bacterial community structure. Proteobacteria has also been reported from many studies based on the 16SrRNA analysis of hot springs with moderately high and very high temperatures (44-110°C) at various geographical locations, including India [15][16][17].…”
Section: Resultssupporting
confidence: 78%
“…There are studies supporting and substantiating findings of the present study that bacterial communities in the hot springs located on the high altitude are dominated by Proteobacteria [12]. Similar observations have been made by [13,14] that geographic locations play a significant role in bacterial community structure. Proteobacteria has also been reported from many studies based on the 16SrRNA analysis of hot springs with moderately high and very high temperatures (44-110°C) at various geographical locations, including India [15][16][17].…”
Section: Resultssupporting
confidence: 78%
“…This variation may be due to high temperature and altitude of the studied hot spring where oxygen concentration is low. Another study [8] reported aerobic culturables only from Ladakh hot springs, and found Proteobacteria, Firmicutes and Actinobacteria but not Bacteroidetes. Paludibacter does not require oxygen, nitrate, sulfate, thiosulfate, elemental sulfur, sulfite, and Fe(III) nitrilotriacetate as terminal electron acceptors [18].…”
Section: Bacterial Diversitymentioning
confidence: 96%
“…1 g soil sample with 9 ml of hot spring water was shaken for 1 h with glass beads on a horizontal shaker. This soil suspension was centrifuged and supernatant was used for assaying the activity using 2 mM ABTS at different pH (5,6,7,8) and temperatures (55-75°C).…”
Section: Phenol Oxidase (Laccase) Activitymentioning
confidence: 99%
See 1 more Smart Citation